Dit hjem er et minefelt! Om politisk satire i Martin Crimps »Advice to Iraqi Women« - Thygesen, Mads (Peripeti, 2021)
Taking the vocabulary of French philosopher Gilles Deleuze as a methodological point of departure, Mads Thygesen writes about political satire in Advice to Iraqi Women (2003) by Martin Crimp.